Effect of rounding on expected value and standard deviation - Cedilnik, Anton (Metodološki zvezki, 2005)
We prove that the rounded expected value of the rounded random variable differs from the expected value of the original random variable by less then 2, where is the distance between two neighbouring rounded numbers. The same conclusion holds for standard deviation. Hence, in practice the influence of rounding to expected value and standard deviation is almost negligible.
Keywords: statistika; standardna deviacija; pričakovana vrednost; verjetnostni račun